New business strategy to turn around sales performance in the future: Case of Siemens Indonesia - Innovator; Deddy Priatmodjo Koesrindartoto; Anh Dung Do MBA (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2023)
This study aims to investigate market conditions, customer behaviour, customer experience, and customer expectations of a company, as well as recommend effective new business strategies with implementation plans and schedules. This study uses qualitative and quantitative methods, with primary data collected through interviews and questionnaires and secondary data obtained from publications, articles, books, and other official sources. The results of this study reveal that the sources of problems are both internal and external, including a lack of communication and coordination between business units, a delayed response to customers, low closeness to customers, and a lack of awareness of customer behaviour. External sources include low customer purchasing power, government regulations, market behaviour, company competitors, and customer expectations. To improve business performance, companies must make changes in approach, including improving customer response time, changing marketing strategies, collaborating with local companies to expand markets, assigning key account managers to new target markets, standardising processes between business units, appointing project leaders when several units participate, and offering competitive rates. Through this research, companies can gain valuable insights and implement more effective business strategies to succeed in challenging markets.